Effects of acceptance and commitment therapy on fatigue interference in patients with advanced lung cancer and caregiving burden: protocol for a pilot randomised controlled trial - Cho Lee Wong; Huiyuan Li; Xiaohuan Jin; Nina Wang; Zhengkun Shi (BMJ Open)
Introduction Cancer-related fatigue is common in patients with advanced lung cancer. It not only interferes with patients’ health-related quality of life, but also increases the caregiving burden of their caregivers. Acceptance and commitment therapy is emerging as a novel way to advocate accepting negative experiences and taking effective actions based on their own values to help patients commit meaningful actions in the course of cancer diseases. This trial aims to test the feasibility, acceptability and preliminary effects of acceptance and commitment therapy for fatigue interference in patients with advanced lung cancer and the caregiver burden.Method and analysis A two-arm, assessor-blind pilot randomised controlled trial will be conducted. A total of 40 advanced lung cancer patient–caregiver dyads, who live in rural areas, will be recruited from a university-affiliated hospital in central China. The participants will be randomised to receive an online six-session acceptance and commitment therapy (i.e. involving metaphors, experiential exercises and mindfulness exercises facilitated by virtual reality technology) plus health education (intervention group, n=20) or health education (control group, n=20). Outcomes will be measured at baseline and 1 week postintervention. The primary outcomes are study feasibility (i.e. eligibility rate, recruitment rate, attrition rate and adherence rate), fatigue interference and caregiver burden. The secondary outcomes are health-related quality of life, meaning in life, psychological flexibility and mindful attention. Semistructured interviews will be conducted to explore the feasibility and experiences of the intervention in a subsample of 10 participants from the intervention group.Ethics and dissemination This study has been approved by the Joint Chinese University of Hong Kong-New Territories East Cluster Clinical Research Ethics Committee (CREC Ref. No. 2023.030) and the Medical Ethics Committee of Xiangya Hospital Central South University (No. 202305336). The findings will be disseminated in peer-reviewed journals and through local or international conference presentations.Trial registration number NCT05885984.